Pengembangan Model Manajemen Pendidikan Karakter di Sekolah Berbasis Kearifan Budaya Lokal (Suku Samin) - Silviana Winty Wongarso; Yari Dwikurnaningsih; Sophia Tri Satyawati (Universitas Kristen Satya Wacana, 2022)
The objective of this study is to describe the management of character education, the obstacles and drawbacks of character education management which is currently being carried out in schools. This research also describes the development of a character education management model in schools based on local cultural wisdom (Samin Tribe). This research is a research and development (RnD) with a qualitative descriptive method with an ethnographic approach which is limited to the product manufacturing stage. Data were collected using document study techniques, observation, and in-depth interviews. The Miles and Huberman model was used to analyze the data. The results of the study: 1) The management of character education that has been implemented in schools shows that the development of character education has been carried out in accordance with character education according to the Ministry of National Education and government regulations, but has not been maximized. This is due to several problems such as the lack of reading resources, model guidebooks on character education, the management of character education carried out in schools has not been in accordance with the four management functions, 2) Obstacle and shortcomings of character education management, namely the management function has not been maximized, the absence of team implementation, lack of coordination meetings, lack of integration into classroom-based approaches, school culture, and society, lack of teacher insight, limited sources of reading books and model guidebooks, 3) Model development which includes character education for the Samin Tribe, then developed through four management functions, namely planning, organizing, implementing, and evaluating which are described through the character education management model in schools based on local cultural wisdom (Samin Tribe).